Lack of MEF2A Δ7aa mutation in Irish families with early onset ischaemic heart disease, a family based study - Belton Christine; McGlinchey Paul G; Spence Mark; Patterson Chris C; Hughes Anne E; Allen Adrian R; Horan Paul G; Jardine Tracy CL; McKeown Pascal P (BMC, 2006)
Abstract Background Ischaemic heart disease (IHD) is a complex disease due to the combination of environmental and genetic factors. Mutations in the MEF2A gene have recently been reported in patients with IHD. In particular, a 21 base pair deletion (Δ7aa) in the MEF2A gene was identified in a family with an autosomal dominant pattern of inheritance of IHD. We investigated this region of the MEF2A gene using an Irish family-based study, where affected individuals had early-onset IHD. Methods A total of 1494 individuals from 580 families were included (800 discordant sib-pairs and 64 parent-child trios). The Δ7aa region of the MEF2A gene was investigated based on amplicon size. Results The Δ7aa mutation was not detected in any individual. Variation in the number of CAG (glutamate) and CCG (proline) residues was detected in a nearby region. However, this was not found to be associated with IHD. Conclusion The Δ7aa mutation was not detected in any individual within the study population and is unlikely to play a significant role in the development of IHD in Ireland. Using family-based tests of association the number of tri-nucleotide repeats in a nearby region of the MEF2A gene was not associated with IHD in our study group.